2022
DOI: 10.7759/cureus.21519
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Diagnosing Foreign Bodies in Children

Abstract: Foreign body aspiration in children is a medical emergency that is associated with significant morbidity and requires medical intervention. The variability of clinical presentations results in delayed diagnosis and treatment. Hence, a high index of clinical suspicion and a thorough examination is needed to expedite the management. We report the case of a toddler girl who aspirated a piece of peanut and was diagnosed as having bronchopneumonia upon presentation with respiratory symptoms for six days. Rigid bron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…A retrospective review done between June 2011 and June 2016 in a Malaysian tertiary academic institution revealed that older children tend to not inform their caretaker of choking episodes which leads to misdiagnosis of asthma [ 4 ]. Other misleading initial diagnoses include bronchiolitis, pneumonia, and laryngitis, as reported by Cassol et al [ 5 ]. Complications severity usually depends on the time lag from the onset of aspiration to diagnosis [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A retrospective review done between June 2011 and June 2016 in a Malaysian tertiary academic institution revealed that older children tend to not inform their caretaker of choking episodes which leads to misdiagnosis of asthma [ 4 ]. Other misleading initial diagnoses include bronchiolitis, pneumonia, and laryngitis, as reported by Cassol et al [ 5 ]. Complications severity usually depends on the time lag from the onset of aspiration to diagnosis [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Sahadan et al, children under the age of three had the highest rate of accidental ingestion and aspiration due to their propensity for placing objects in their mouths, crying, or playing with them while doing so [ 5 ]. Due to this habit, another complication that is commonly reported is the impaled foreign body due to the aspiration of the object [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common location of affected lung lobe is the right lower lobe because it is larger and more vertical. Bilateral lower lung lobes are usually affected by aspiration during standing while alcoholics who aspirate in a prone position may have right upper lobe infiltrated commonly [25].…”
Section: Epidemiologymentioning
confidence: 99%